The pathway leading individuals to undergo the German Dual VET system in Brazil - Kauer, Marcelo [Verfasser] (My University, 2014)
Since 1984, the private vocational school in Sao Paolo offers German dual vocational education and training (VET) at secondary level in cooperation with the Chamber of Commerce and Industry Brazil-Germany (AHK) and serveral other companies. This article discusses "three important conditions leading individuals to seek the German dual system in Brazil. In addition, a brief explanation of the functional mechnisms associated with this educational pathway by former apprentices is presented." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; I 2.3.3 Lateinamerika; Duales System; Transfer; Ausbildungswahl; Brasilien